The quality and utility of research in ectopic pregnancy in the last three decades: An analysis of the published literature. (February 2020) - Kemper, James M.; Wang, Hannah T.Y.; Ong, Alston G.J.; Mol, Ben W.; Rolnik, Daniel L.
Abstract: Objective: Ectopic pregnancy is a potentially life-threatening health problem that affects fertility and generates a significant economic burden. Optimal management, including when to choose methotrexate, and whether to do salpingectomy or salpingostomy, is still unclear. This study aimed to assess the quality and utility of research on ectopic pregnancy in the last three decades. Study design: We analyzed the quantity, quality and utility of the published literature, including 6, 309 articles published over a 30-year period. We searched PubMed for studies on ectopic pregnancy, with subsequent analysis utilizing bibliometric network maps. Consolidated Standards of Reporting Trials (CONSORT) guidelines and a newly adapted checklist for usefulness of research were applied to assess randomized controlled trial (RCT) quality. Results: The initial search returned 14, 727 articles, of which, after filters of publication date (1987/01/01 to 2017/12/31), species (Human) and language (English) were applied, 6, 309 articles remained. The number of publications each year remained relatively stable, with a mean number of 280 articles published three decades ago versus 248 articles published on average in the last decade. The 7, 733 human species articles published between 1987–2017 were written in 27 different languages, with 82 % in English. Publications in 14 selected high-impact journals accounted for 26.5 % (1, 673/6, 309) of all articles, with on average 54 publications per year across three decades. An increase in systematic reviews and meta-analyses (+1000 %), and case reports (+53 %) was seen between 1987–2017, while the percentage of RCTs (–25 %) decreased. The analyzed RCTs were of moderate quality, and few addressed the most important clinical questions. Conclusion: In the last three decades, both the number of articles on ectopic pregnancy and the number of articles in high-impact journals have remained stable. Despite these constant numbers, the quality of RCTs was suboptimal and there was a decrease in the annual number of published RCTs, while the use of meta-analysis significantly amplified. This study suggests continued review of research practices and provides suggestions on how the quality of the published literature can be improved.